Conflict, Job Stress, Satisfaction and Its Effect on Performance - Zacharias, Tehubijuluw (Syntax Corporation, 2024)
This study aims to analyze conflict, work stress, satisfaction and influence on employee performance. This study uses a dextive-quantitative approach with the correlational type of cause-effect. The study was conducted in the Ambon Class I Navigation District. This research was conducted for 2 (two) months. The population used in this study was that all Ambon class I Navigation District employees were 31 people. The sample determination method is full sampling. Data was analyzed using multiple linear regression analysis. The results of the study concluded that (1) conflict had a negative and significant effect on the performance of Ambon Class I Navigation District employees; (2) Work stress has a negative and significant effect on the performance of Ambon Class I Navigation District employees; (3) Satisfaction has a positive and significant effect on the performance of the Ambon Class I Navigation District Employees and (4) Conflict, Work Stress and Satisfaction have a significant effect on the performance of the Ambon Class I Navigation District Employees.